Scholarship Decision Support System At Bina Sarana Informatika Cikampek Using The Method Simple Additive Weighting (Saw) - Jaelani, Irsan; Kurniawan, Imay; Singasatia, Dayan; Dewi Lestari, Chandra; Khoirullah, Andre (RISTEC : Research in Information Systems and Technology, 2023)
Scholarships are a form of appreciation in the form of financial assistance given to individuals or organizations for the work achievements they have produced. The award can be in the form of funding or certain access to an institution in the form of financial assistance for learning activities. In this research, the Simple Additive Weighting method was used to determine which students were entitled to receive the scholarship by assigning criteria and weights to each student so that it looked more detailed. Of the six alternatives used as case examples in this research, there is one alternative that is recommended as a student who is entitled to a scholarship, namely the alternative with a calculation result of 1.9.